Tinjauan Evaluasi Motif Merger-Akuisisi dalam Perspektif Kinerja Keuangan - Andi Saputra; Alydia Hasna Syifahayati; Amar Khosyian; Desilva Rizki Selarasati; Devina Martha Giovanni Napitupulu; Dinda Amelia Asyifa; Arwan Gunawan (Politeknik Negeri Bandung, 2021)
Tinjauan Evaluasi Motif Merger-Akuisisi dalam Perspektif Kinerja Keuangan